Adenovirus Vectors and Subviral Particles for Protein and Peptide Delivery - W. Kron, Matthias; Kreppel, Florian (Current Gene Therapy, 2012)
Adenovirus vectors belong to the most frequently used vector type in gene therapy approaches. In addition, adenovirus vector particles and adenovirus subviral particles offer a great potential for the direct delivery of proteins into cells. In this review we discuss this potential and the technology of adenovirus as a protein delivery platform for applications ranging from vaccination to gene therapy.
Keywords: adenovirus subviral particles